Cohort profile: Nordic Helicobacter Pylori eradication project (NordHePEP). (4th May 2023) - Pettersson, Anna-Klara; Santoni, Giola; Yan, Jacinth; Radkiewicz, Cecilia; Xie, Shaohua; Birgisson, Helgi; Ness-Jensen, Eivind; von Euler-Chelpin, My; Kauppila, Joonas H.; Lagergren, Jesper
Abstract: Purpose: This cohort description presents the Nordic Helicobacter Pylori Eradication Project (NordHePEP), a population-based cohort of patients having received eradication treatment for Helicobacter pylori (HP). The cohort is created with the main purpose of examining whether and to what extent HP eradication treatment influences the risk of gastrointestinal cancer. Participants: NordHePEP includes all adults (aged ≥18 years) having been prescribed and dispensed HP eradication treatment according to the nationwide complete drug registries in any of the five Nordic countries (Denmark, Finland, Iceland, Norway, or Sweden) between 1994 and 2020 (start and end year varies between countries). We have retrieved and merged individual-level data from multiple national registries, including drug, patient, cancer, population, and death registries. Findings: The cohort includes 674, 771 patients having received HP eradication treatment. During up to 23 years of follow-up, 59, 292 (8.8%) participants were diagnosed with cancer (non-melanoma skin cancer excluded), whereof 15, 496 (2.3%) in the gastrointestinal tract. Future plans: We will analyse HP eradication treatment in relation to gastrointestinal cancer risk. Standardised incidence ratios will be calculated as the observed cancer incidence in the cohort divided by the expected cancer incidence, derived from the background population of the corresponding age, sex, and calendar year.